Urban air environmental health indicators for Kuala Lumpur City (Indikator kesihatan persekitaran udara bandar untuk Bandaraya Kuala Lumpur) - Oliver, Ling Hoon Leh; Shaharuddin Ahmad; Kadaruddin Aiyub; Yaakub Mohd. Jani; Ting, Kien Hwa (Universiti Kebangsaan Malaysia, 2012)
Air environmental health indicators were defined operationally as a combination of “air quality” and “air-related health” indicators. Clean air is a basic precondition of human health. Air pollutants had been identified with potential negative impact on health especially on respiratory and cardiovascular diseases. Thus, studies are necessary to identify and understand the state of environmental health. This study was aimed to examine and analyse the air environmental health condition in city of Kuala Lumpur by using a set of indicators. House to house questionnaire survey was carried out to collect air-related health data, and air quality sampling was carried out to identify ambient air quality level of the city. In general, city of Kuala Lumpur was found to have a “moderate level” of air quality. Air-related illnesses indicated by acute respiratory infection and asthma were found to be higher in more developed or higher density zones, as compared to other zones. Besides, air-related illnesses were significantly correlated to respondents’ exposure to air pollution. The findings imply that human health can be improved by managing the urban development and its environmental quality properly.